Thalidomide in treatment of connective diseases and vasculities - D. Ribatti; F.P. Cantatore; N. Maruotti (PAGEPress Publications, 2011)
Thalidomide is an immunomodulatory, anti-inflammatory and anti-angiogenic drug. Thalidomide exerts its effects by decreasing circulating CD4 positive T-cells and stimulating CD8 positive T-cells, by increasing the number of Natural Killer cells and T-helper 2 cells. Thalidomide also inhibits proliferation of stimulated T-cells and leukocyte chemotaxis. It modifies a number of integrin receptors and other leukocytic surface receptors and down-modulates cell-adhesion molecules involved in leukocyte migration. It has been demonstrated that thalidomide inhibits TNFa, IL-5, IL-6, IL-8, IL-12 production and increases production of IL-2, IL-10 and INFg. Moreover thalidomide plays an important role in inhibition of VEGF and FGF-2 mediated angiogenesis. Although the exact mechanism of action is not fully understood and only limited treatment opinions exist, thalidomide plays a role also in connective diseases and vasculities. Thalidomide has been seen efficacious in the treatment of cutaneous disorders in patients with systemic lupus erythematosus and in mucocutaneous disease in Behçet's disease with a not dose-dependent response, even if it should be restricted to selected patients because of its important side effects.